Role of NF-Y in In Vivo Regulation of the γ-Globin Gene - Duan, Zhijun (American Society for Microbiology, 2001)
The duplicated CCAAT box is required for γ gene expression. We report here that the transcriptional factor NF-Y is recruited to the duplicated CCAAT box in vivo. A mutation of the duplicated CCAAT box that severely disrupts the NF-Y binding also reduces the accessibility level of the γ gene promoter, affects the assembly of basal transcriptional machinery, and increases the recruitment of GATA-1 to the locus control region (LCR) and the proximal promoter and the recruitment of transcription cofactor CBP/p300 to the LCR. These findings suggest that recruitment of NF-Y to the duplicated CCAAT box plays a role in the chromatin opening of the γ gene promoter as well as in the communication between the γ gene promoter and the LCR.